2013
DOI: 10.7763/jocet.2013.v1.12
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Coefficients of UAE Gasoline as Inputs to Some Environmental Transport or Risk Assessment

Abstract: Vapor diffusion was studied from volatile liquids of three brands of UAE gasoline: Super, Special, E+ and a mixture of these brands. The studying was conducted at 50 oC which represent the highest atmospheric temperature in UAE. The diffusion coefficients of Super gasoline ( 98 Octane number) was equal to 6.348 E-07, for special gasoline ( 95 octane number) equal to 7.353 E-07, for E+ (octane number 91) equal to 2.169 E-06, and the mixture of these three brands is 6.302E-07 m2/s. This concluded that super gaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
4
0
2
Order By: Relevance
“…The gravimetric method, which employs weight measurements over time, was used to determine the transport parameters, such as partition coefficient (K), diffusion coefficient (D) and mass flux (F) (Glaza and Park, 1992; Kim et al, 1996; Park and Bontoux, 1991, 1993; Park and Nibras, 1993; Sangam and Rowe, 2005). As this method measures weight gain, the determined values are for the mixture of chemicals present in gasoline and mineral spirits (Al Zubaidy et al, 2013; Park and Nibras, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…The gravimetric method, which employs weight measurements over time, was used to determine the transport parameters, such as partition coefficient (K), diffusion coefficient (D) and mass flux (F) (Glaza and Park, 1992; Kim et al, 1996; Park and Bontoux, 1991, 1993; Park and Nibras, 1993; Sangam and Rowe, 2005). As this method measures weight gain, the determined values are for the mixture of chemicals present in gasoline and mineral spirits (Al Zubaidy et al, 2013; Park and Nibras, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…For water vapor, the simplifying assumption z 0v = z 0 /10 is often employed (Brutsaert, 2005). Since the diffusion coefficient of gasoline vapor, e.g., D ma = 7 ×10 −7 m 2 /s (Al Zubaidy et al, 2013), is roughly equal to the one of water vapor (10 −6 m 2 /s), the Schmidt numbers for the two vapors are also about equal. Therefore theoretical considerations (Brutsaert, 1975) suggest that z 0v = z 0 /10 is also a reasonable approximation for gasoline vapor.…”
Section: Potential Evaporation Modelingmentioning
confidence: 98%
“…The assessment was conducted at 48°C, which represents the highest atmospheric temperature in the UAE. The researchers found that super gasoline has a higher octane number, minimum density, and a diffusion coefficient of 6.348 (Alzubaidy et al , 2013).…”
Section: Literature Reviewmentioning
confidence: 99%